The crime in mind: criminal responsibility and the Victorian novel - Rodensky, Lisa (Oxford Univ. Press, 2003)
Organizing crime : conduct and character in Oliver Twist : prologue to George Eliot's crimes -- "To fix our minds on that consequence" : minding consequences in Adam Bede and Felix Holt -- Middlemarch, Daniel Deronda, and the crime in mind -- James Fitzjames Stephen and the responsibilities of narrative -- Modern responsibilities